Association of Picornavirus Infections With Acute Otitis Media in a Prospective Birth Cohort Study. (28th February 2020) - Seppälä, Elina M; Oikarinen, Sami; Lehtonen, Jussi P; Neupane, Subas; Honkanen, Hanna; Tyni, Iiris; Siljander, Heli; Ilonen, Jorma; Sillanpää, Saara; Laranne, Jussi; Knip, Mikael; Hyöty, Heikki
Abstract: Background: Human rhinoviruses (HRVs), human enteroviruses (HEVs) and human parechoviruses (HPeVs) have been linked to acute otitis media (AOM). We evaluated this association in a prospective birth cohort setting. Methods: A total of 324 healthy infants were followed up from birth to age 3 years. Nasal swab samples were collected at age 3, 6, 12, 18, 24, and 36 months and screened for HRV and HEV using real-time reverse-transcription quantitative polymerase chain reaction. Stool samples were collected monthly and analyzed for HRV, HEV, and HPeV. AOM episodes diagnosed by physicians were reported by parents in a diary. The association of viruses with AOM was analyzed using generalized estimation equations, and their relative contributions using population-attributable risk percentages. Results: A clear association was found between AOM episodes and simultaneous detection of HEV (adjusted odds ratio for the detection of virus in stools, 2.04; 95% confidence interval, 1.06–3.91) and HRV (1.54; 1.04–2.30). HPeV showed a similar, yet nonsignificant trend (adjusted odds ratio, 1.44; 95% confidence interval, .81–2.56). HRV and HEV showed higher population-attributable risk percentages (25% and 20%) than HPeV (11%). Conclusions: HEVs and HRVs may contribute to the development of AOM in a relatively large proportion of cases. Abstract : Human rhinoviruses and human enteroviruses are associated with acute otitis media (AOM) in young children and may contribute to the development of AOM in a relatively large proportion of cases.